1979
DOI: 10.1037/0022-3514.37.9.1539
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional messages of smiling: An ethological approach.

Abstract: Did smiling evolve as an expression of happiness, friendliness, or both? Naturalistic observation at a bowling alley (N-1,793 balls) shows that bowlers often smile when socially engaged, looking at and talking to others, but not necessarily after scoring a spare or a strike. In a second study, bowlers (N =166 balls) rarely smiled while facing the pins but often smiled when facing their friends. At a hockey game, fans (N = 3,726 faces) smiled both when they were socially involved and after events favorable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
258
3
9

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(284 citation statements)
references
References 12 publications
14
258
3
9
Order By: Relevance
“…The authors reported that 29 out of 40 judo fighters displayed Duchenne smiles after winning a gold-or bronze-medal match. Matsumoto and Willingham concluded that sociality was not a variable related to the display of smiles, and previous findings supporting a link between smiling and social interaction (Fernández-Dols & Ruiz-Belda, 1995;Kraut & Johnston, 1979;Ruiz-Belda et al, 2003) were actually nonfindings because of methodological flaws. Matsumoto and Willingham (2006, p. 576) wrote: "[Our] results contrast to the findings of previous field studies reporting nonfindings (Fernández-Dols & Ruiz-Belda, 1995;Kraut & Johnston, 1979;Ruiz-Belda et al, 2003).…”
Section: The Ethological Approach To the Social And Emotional Messagementioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that 29 out of 40 judo fighters displayed Duchenne smiles after winning a gold-or bronze-medal match. Matsumoto and Willingham concluded that sociality was not a variable related to the display of smiles, and previous findings supporting a link between smiling and social interaction (Fernández-Dols & Ruiz-Belda, 1995;Kraut & Johnston, 1979;Ruiz-Belda et al, 2003) were actually nonfindings because of methodological flaws. Matsumoto and Willingham (2006, p. 576) wrote: "[Our] results contrast to the findings of previous field studies reporting nonfindings (Fernández-Dols & Ruiz-Belda, 1995;Kraut & Johnston, 1979;Ruiz-Belda et al, 2003).…”
Section: The Ethological Approach To the Social And Emotional Messagementioning
confidence: 99%
“…Requirement (a) was unfulfilled in the studies with happy bowlers, and -to some extent -to hockey and soccer fans' studies (Kraut & Johnston, 1979;Ruiz-Belda et al, 2003), but it was fulfilled in Fernández-Dols and Ruiz-Belda's (1995) study with gold medalists. Requirement (b) was unaccomplished by Kraut and Johnston's study, which was carried out in 1979 -when video recordings were unusualbut it was also ignored by Willingham (2006, 2009), who based their findings on an unsystematic sample of still photographs taken by a sports photographer.…”
Section: The Ethological Approach To the Social And Emotional Messagementioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is important to note that a number of emotion theories and recent empirical studies suggest that both men and women's expressive behavior is particularly susceptible to modification by various social factors (e.g., Buck, Losow, Murphy, & Costanzo, 1992;Ekman & Friesen, 1975;Ekman et al, 1982;Fridlund, 1994;Frijda, 1993;Gross & John, 1997;Halberstadt et al, 1995;Kraut & Johnson, 1979;Levenson, 1994). Indeed, expressivity serves both informative and evocative functions in the social environment (Keltner, 1996).…”
mentioning
confidence: 99%
“…This view is supported by the observation that emotional expressions have significant impacts on perceivers in a variety of domains: social inferences (Hess et al 2000;Knutson 1996), competitive interactions (Camras 1980), and cooperative actions (Brown et al 2003;Mehu et al 2007a, b). In addition, emotional expressions are particularly salient in social contexts (Kraut and Johnston 1979;Parkinson 2005). Still, emotional expressions have also been shown to provide individual benefits through emotional regulation (Gross and Levenson 1997;Keltner and Bonanno 1997;Papa and Bonanno 2008) but also through enhanced sensory acquisition .…”
Section: The Production and Perception Of Social Signals And Cuesmentioning
confidence: 99%